The Influence of Islamic Religious Education on the Character Development of Adolescents at YPP Sawit Sebrang Private Senior High School - Rusdi, M. Sani Hafiz (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to determine the influence of Islamic Religious Education on the character development of adolescents at YPP Sawit Sebrang Private Senior High School. The research method employed is a quantitative approach using a survey technique through questionnaires distributed to students as respondents. The data obtained were analyzed using statistical techniques to examine the relationship and influence of Islamic Religious Education on character development. The results indicate that Islamic Religious Education has a significant impact on shaping students’ Islamic personality, particularly in terms of discipline, responsibility, and religious attitudes. Thus, it can be concluded that Islamic Religious Education plays an important role in developing adolescents’ character in accordance with Islamic values within the school environment.